Chances of fully fledged employment after a dual-system apprenticeship - Maier, Tobias [Verfasser]; Dorau, Ralf [Verfasser] (My University, 2011)
"A smooth transition from initial vocational training into employment is a fundamental pre - requisite for establishing successful career trajectories. However, not all young people who complete a dual-system apprenticeship negotiate this “second threshold” transition with uniformly positive results. An analysis of Microcensus data shows that outcomes vary depending on the level of school-leaving qualifications and the chosen field of initial vocational training." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.3.3.1 Qualifikationsverwertung; Berufseinmündung; Zweite Schwelle; Ausbildungsabsolvent; Beruflicher Status; Arbeitsmarktchance; Bildungsabschluss; Berufsfeld; Quantitative Angaben